The effect of a combination of nitrogen and phosphorus fertilization with bamboo biochar rate on the growth and productivity of rice - Mahyudi, Mahyudi; Purwanto, Benito Heru; Hanudin, Eko (Faculty of Agriculture, Universitas Gadjah Mada jointly with PISPI, 2024)
The combination of fertilizer treatment with biochar has shown to be a sustainable and ecologically friendly method of increasing soil fertility and crop productivity. However, its combined impact on nutrient availability and rice yield is still unclear. This study aimed to investigate the effect of bamboo biochar produced by the Kontiki method in combination with nitrogen and phosphorus fertilization on nutrient availability in the soil and the productivity of rice. The treatment factors included the fertilizer combination factor (B) consisting of B1 (N + P fertilizer + Biochar), B2 (N fertilizer + Biochar), B3 (P fertilizer + Biochar), and B4 (Biochar + no fertilizer), and the biochar dose factor (F) comprising F0 (0 tons ha⁻¹), F1 (5 tons ha⁻¹), and F2 (10 tons ha⁻¹), resulting in 36 experimental plots with 12 treatment combinations. Measurement of ammonium and nitrate concentration in the soil started on the 15th day after planting, following the measurement of the growth of rice plant biomass with an interval of 15 days. The measurement of available P in the soil was started on day 45 after planting and continued until harvesting time with the same time intervals as the measurements of ammonium and nitrate. The study found that combining bamboo biochar treatment with nitrogen and phosphorus fertilizer greatly boosted the availability of nitrogen (ammonium and nitrate) and availability of P in the soil. Treatment combinations improved lowland rice yield (P < 0.05) by increasing plant height, number of tillers, dry weight of shoots and roots, grain weight per clump, 1000-grain weight, and grain yield.